2015
DOI: 10.1371/journal.pone.0120419
|View full text |Cite
|
Sign up to set email alerts
|

Association between Resistin Levels and All-Cause and Cardiovascular Mortality: A New Study and a Systematic Review and Meta-Analysis

Abstract: ContextStudies concerning the association between circulating resistin and mortality risk have reported, so far, conflicting results.ObjectiveTo investigate the association between resistin and both all-cause and cardiovascular (CV) mortality risk by 1) analyzing data from the Gargano Heart Study (GHS) prospective design (n=359 patients; 81 and 58 all-cause and CV deaths, respectively); 2) performing meta-analyses of all published studies addressing the above mentioned associations.Data Source and Study Select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 27 publications
6
49
1
2
Order By: Relevance
“…Each 10 ng/ml higher serum resistin was associated with a 17% higher risk of death even after adjusting for confounders such as socio-demographic parameters, residual kidney function, nutritional/inflammatory parameters, comorbidities, and transplantation-related covariates. Our findings are similar to what was recently described across various types of heterogeneous populations in a meta-analysis, although not all studies detected a resistin-mortality association [32,33]. There are several different pathways that may explain the association between resistin and death.…”
Section: Discussionsupporting
confidence: 91%
“…Each 10 ng/ml higher serum resistin was associated with a 17% higher risk of death even after adjusting for confounders such as socio-demographic parameters, residual kidney function, nutritional/inflammatory parameters, comorbidities, and transplantation-related covariates. Our findings are similar to what was recently described across various types of heterogeneous populations in a meta-analysis, although not all studies detected a resistin-mortality association [32,33]. There are several different pathways that may explain the association between resistin and death.…”
Section: Discussionsupporting
confidence: 91%
“…47 including 7 studies reported that circulating resistin levels were associated with mortality, especially in high-risk individuals, such as patients with diabetes. 8 Diabetic patients have been reported to have higher levels of resistin compared to non-diabetic patients, suggesting some specific role of resistin in this high-risk population. 9,10 In older adults, inflammatory markers, such as interleukin-6 (IL-6), C-reactive protein (CRP), and tumor necrosis factor-alpha (TNF-alpha) have been independently associated with CVD events with an incremental improvement of prediction.…”
Section: Introductionmentioning
confidence: 96%
“…2G and H). Human resistin is a proinflammatory cytokine expressed in and secreted by monocytic cells, and a recent metaanalysis provided evidence for an association between higher circulating resistin levels and increased mortality (28,29). Furthermore, resistin gene expression is positively correlated with insulin resistance in humans.…”
Section: Discussionmentioning
confidence: 99%